Colorimetric Plasmon Resonance Imaging Using Nano Lycurgus Cup Arrays. Issue 1 (31st January 2013) - Gartia, Manas Ranjan; Hsiao, Austin; Pokhriyal, Anusha; Seo, Sujin; Kulsharova, Gulsim; Cunningham, Brian T.; Bond, Tiziana C.; Liu, Gang Logan
<x xml:space="preserve">Abstract</x> A large‐area high‐density nanoscale Lycurgus cup array is created with 100 times better sensitivity than any other reported nanoplasmonic device. With this device, nanoplasmonic spectroscopy sensing, for the first time, becomes colorimetric sensing requiring only the naked eye or ordinary visible color photography. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>